Cardicola aurata sp. n. (Digenea: Sanguinicolidae) from Mediterranean Sparus aurata L. (Teleostei: Sparidae) and its unexpected phylogenetic relationship with Paradeontacylix McIntosh - Holzer, A. S.; Montero, F. E.; Repullés, A.; Nolan, M. J.; Sitj-Bobadilla, A. à.; Alvarez-Pellitero, P.; Zarza, C.; Raga, J. A. (Parasitology International, 2008)
A new sanguinicolid trematode, Cardicola aurata sp. n., is described from gilthead seabream Sparus aurata L., from off the Spanish Mediterranean coast. The morphology of C. aurata sp. n. generally agrees with the diagnosis of the genus, however, in contrast to all other reported Cardicola spp. the male pore is located sub-medially at the posterior end of the body instead of sinistrally before the posterior end of the body. Based on a comparison of the morphology as well as partial 28S and ITS2 rDNA sequence data from the present species with that from closely related species, it was decided to emend the diagnosis of Cardicola rather than create a new genus, as the aberrant position of the male pore is likely to be an autapomorphy. The phylogenetic analyses revealed a close relationship between Cardicola and Paradeontacylix, two genera with considerable morphological differences; C. aurata sp. n. occupies a position intermediate to these genera. Thus, a morphological comparison of Cardicola, Paradeontacylix and Braya, a genus which is morphologically similar to Cardicola but clusters basal to the Cardicola/Paradeontacylix clade, was conducted. The results of this comparison showed that despite large differences with regard to body shape, the organisation of the internal organs is very similar in species of Cardicola and Paradeontacylix. The synopsis of morphological data and molecular phylogeny allows for interpretations regarding the importance of different morphological features for the phylogenetic inference of the Sanguinicolidae.